Inhibiting lncRNA NEAT1 Increases Glioblastoma Response to TMZ by Reducing Connexin 43 Expression - Jinxing Liang; Jia‐xiu Xie; Junhui He; Yi Li; Dongmei Wei; Rongfei Zhou; Guining Wei; Xuehua Liu; Qiudan Chen; Dongmei Li (Cancer Reports, 2024)
ABSTRACT Objectives Glioblastoma multiforme (GBM) is considered the most assailant subtype of gliomas, presenting a formidable obstacle because of its inherent resistance to temozolomide (TMZ). This study aimed to characterize the function of lncRNA NEAT1 in facilitating the advancement of gliomas. Methods The expression level of NEAT1 in glioma tissues and cells was detected by qRT‐PCR. RNA interference experiment, cell proliferation assay, FITC/PI detection assay, immunoblotting, bioinformatics prediction, a double luciferase reporter gene assay, RNA immunoprecipitation (RIP) assay, SLDT assay and correlation analysis of clinical samples were performed to explore the regulatory effects of NEAT1, miR‐454‐3p and Cx43 and their role in malignant progression of GBM. The role of NEAT1 in vivo was investigated by an intracranial tumor formation experiment in mice. Results The results showed that recurring gliomas displayed elevated levels of NEAT1 compared to primary gliomas. The suppression of NEAT1 led to a restoration of sensitivity in GBM cells to TMZ. NEAT1 functioned as a competitive endogenous RNA against miR‐454‐3p. Connexin 43 was identified as a miR‐454‐3p target. NEAT1 was found to regulate gap junctional intercellular communication by modulating Connexin 43, thereby impacting the response of GBM cells to TMZ chemotherapy. Downregulation of NEAT1 resulted in enhanced chemosensitivity to TMZ and extended the survival of mice. Conclusions Overall, these results indicated that the NEAT1/miR‐454‐3p/Connexin 43 pathway influences GBM cell response to TMZ and could offer a potential new strategy for treating GBM.